AN ANALYSIS OF TRADITIONAL VERSUS IFRS FINANCIAL STATEMENTS OF BRAZILIAN PUBLIC COMPANIES FOR THE YEARS 2009 AND 2010 - Ana Clara Lacerda de Oliveira; Sirlei Lemes (European Scientific Journal, ESJ, 2013)
The aim of this paper is to analyze the effect of adopting International Accounting Standards on the accounting statements of Brazilian public companies that are quoted in the São Paulo Stock Exchange Index (IBOVESPA). We analyze financial statements that were disclosed in 2009 and retransmitted in 2010 for 57 public companies. Difference of mean tests were carried out for the following indicators in the statements: third party participation (debt) debt composition, immobilization of non-current resources, net liquidity, general liquidity, and return on net worth. Results show that there was significant decrease in the debt composition index upon change to the new accounting practice. The difference has been confirmed though the "test t" for dependant samples with both indicators which presented a normal distribution. As for the debt indicators, immobilization of non-current resources, net liquidity, general liquidity, and return on net worth, there was no significant difference in values. However, it's noticeable in the financial statements in general, the increase in the comparability of the information among companies and the transparency of the financial statements, and also improvement of both quality and quantity of the information exposed to stakeholders and responsible authorities.